2020
DOI: 10.1103/physrevresearch.2.033275
|View full text |Cite
|
Sign up to set email alerts
|

Rheotaxis of spheroidal squirmers in microchannel flow: Interplay of shape, hydrodynamics, active stress, and thermal fluctuations

Abstract: Microswimmers exposed to microchannel flows exhibit an intriguing coupling between propulsion, shape, hydrodynamics, and flow which gives rise to distinct swimming behaviors. We employ a generic coarse-grained model of prolate spheroidal microswimmers, denoted as squirmers, exposed to channel flow to shed light onto their transport properties. The embedding fluid is implemented by the multiparticle collision dynamics approach (MPC), a particle-based mesoscale simulation method, which includes thermal fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…Rheotaxis of spermatozoa was first reported more than half a century ago (Bretherton & Rothschild 1961), and the underlying mechanism is understood to be the interplay among fluid shear, steric surface interactions and the chirality of the flagellar beat (Miki & Clapham 2013;Kantsler et al 2014;Omori & Ishikawa 2016). Similar wall-mediated rheotaxis has been reported for bacteria (Hill et al 2007;Ishikawa et al 2014;Mathijssen et al 2019), autophoretic Janus rods (Brosseau et al 2019), synthetic bimetallic micromotors (Ren et al 2017) and model squirmers (Ishimoto 2017;Qi et al 2020). Zott & Stark (2012) showed that rheotaxis could be induced by direct collisions with the walls or in a narrow channel.…”
Section: Introductionsupporting
confidence: 60%
“…Rheotaxis of spermatozoa was first reported more than half a century ago (Bretherton & Rothschild 1961), and the underlying mechanism is understood to be the interplay among fluid shear, steric surface interactions and the chirality of the flagellar beat (Miki & Clapham 2013;Kantsler et al 2014;Omori & Ishikawa 2016). Similar wall-mediated rheotaxis has been reported for bacteria (Hill et al 2007;Ishikawa et al 2014;Mathijssen et al 2019), autophoretic Janus rods (Brosseau et al 2019), synthetic bimetallic micromotors (Ren et al 2017) and model squirmers (Ishimoto 2017;Qi et al 2020). Zott & Stark (2012) showed that rheotaxis could be induced by direct collisions with the walls or in a narrow channel.…”
Section: Introductionsupporting
confidence: 60%
“…Several papers have described a similar positive rheotactic response for bimetallic rods [11,12,13] . Interestingly, all of the microswimmers (both biological and artificial) discussed so far possess an anisotropy in shape, and their upstream response can be rationalized by appealing to a so-called "weather vane" mechanism [14,15] : when swimming close to the surface, the swimmer body experiences an attraction to the substrate, and can therefore function as an "anchor" or pivot point. The tail extends away from the surface, into faster fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…We expect hydrodynamic swimmer-wall interactions [47] to affect our results quantitatively, but not fundamentally. Possible emergent behavior due to noise effects [48,49] and chirality of flagella [4] The mobility matrix in the first line of Eqs. ( 1) of the main text mediates the hydrodynamic interaction for the translational degrees of freedom and is given by the Rotne-Prager tensor for differently sized beads [1]…”
Section: Fig 2 (A)mentioning
confidence: 99%